From Apocalypse to Merkabah Mysticism: Studies in the Slavonic Pseudepigrapha. By Andrei A. Orlov - Rowland, Christopher (The journal of theological studies, 2008)
Andrei Orlov's impressive study of the Slavonic Apocalypse of Enoch (The Enoch-Metatron Tradition, 2005) announced the arrival of an important contributor to the discussion of Apocalypticism and its relationship to early Jewish mysticism. This collection of essays, most of which have been published previously, consolidates a formidable international reputation. What is especially important about Orlov's work is that (as he tactfully puts it) the ‘challenge of Slavonic language tends to mean that, for many of us, engagement with the Slavonic texts tends to be in translation only’.